Derivation of two induced pluripotent stem cell lines from a healthy control subject - Dan Zhang; Di Huang; Leon M. Larcher; Khine Zaw; Shang-Chih Chen; Luke Jennings; Tina M. Lamey; Jennifer A. Thompson; Terri L. McLaren; Fred K. Chen; Samuel McLenachan (Stem Cell Research)
Two human induced pluripotent stem cell lines, LEIi021-A and LEIi021-B, were derived from dermal fibroblasts from a healthy control subject from an Australian Aboriginal family with retinitis pigmentosa-11. Reprogramming was performed using episomal vectors expressing OCT4, SOX2, LIN28, L-MYC, KLF4 and mp53DD. Pluripotency markers were expressed in both LEIi021-A and LEIi021-B lines. The two cell lines displayed normal karyotypes and demonstrated the ability to differentiate into embryoid bodies with the three primary germ layers and retinal pigment epithelial cells.